(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
WSNs consist of a large number of small sensor nodes. These nodes are very cheap in terms of cost. In military operations, there is always a threat of being attacked by enemies. So, the use of these cheap sensor nodes will help to reduce the loss. In this paper, we analyze the existing literature of using WSNs for military applications. We will discuss the available scenarios of using sensor nodes in the military uses. Provided suitable sensors the system can detect identify and classify threads based on the count, number, type weather it is armored vehicles or men in foot, type and amount of weapons they carry, etc., can be detected in advance. This system provides reliable real time war picture and better situational awareness. This will further help to improve the troop readiness and decrease the reaction time. Added using the data collected tactical planning for deploying troops effectively can be done. In case of civil applications economic zones like oil fields, gold mines, can be protected from intruders and attackers. Industrial complex and production facility can be protected with minimized man power and improved efficiency. Basic criteria are which had to be taken into account while deploying wireless sensors for such applications has been discussed. Particularly locating the intruder with respect to the distance from the sensor node to the target in terms of latitude and longitudinal coordinates are discussed here.